Synergistic effects of an artificial carbon coating layer and Cu2+-electrolyte additive for high-performance zinc-based hybrid supercapacitors. (15th October 2022) - Peng, Jiaxin; Yu, Juan; Chu, Dewei; Hou, Xueyang; Jia, Xuefeng; Meng, Bicheng; Yang, Kai; Zhao, Junkai; Yang, Naixing; Wu, Jianchun; Li, Linbo
Abstract: Rechargeable aqueous zinc-based hybrid supercapacitors (ZHSC) are widely used because of their safety, high capacity, cost-effectiveness, and environmental friendliness. However, the serious dendrite growth, low cycle life, and poor safety of zinc metal anodes greatly hinder their practical application. Additionally, the lack of excellent cathode materials also restricts further development of high-efficiency aqueous ZHSC. Herein, we report a novel persimmon-branch biomass carbon-based material with a naturally graded pore structure. Persimmon branch activated carbon (PBAC) was used as the cathode, and the anode was constructed using a zinc foil coated with one-step carbonized persimmon branch carbon (PBC). A new type of high-performance ZHSC was assembled using the porous structure of a carbon-based material and Cu 2+ -electrolyte additive. The hierarchical pore structure endowed the activated carbon with excellent electric double-layer capacitance characteristics as well as superb zinc ions storage ability. The artificial carbon-coated zinc metal anodes could homogenize the electric fields, and the Cu 2+ from the electrolyte induced zinc metal deposition, which improved the cycle stability of the ZHSC. Therefore, the assembled ZHSC (PBAC4 |ZnSO4 +CuSO4 |PBC@Zn) exhibited excellent electrochemical performance, high discharge capacity (182.8 mAh g −1 ), good rate performance (51.4 mAh g −1 at 10 A g −1 ), high energy density (27.1 W h kg −1 at 5 kW kg −1 based on the weight of the active material) and demonstrated a long cycle life with 73.8% capacitance retention after 3000 cycles at 5 A g −1 high current density. Graphical abstract: Image 1